Pembuatan Aplikasi Manajemen Kendaraan berbasis Android - Deryan Thimoti Yudianto; Agustinus Noertjahyana; Justinus Andjarwirawan (Jurnal Infra, 2017)
There are many vehicle users that are using Android based smartphones. When using vehicle, the vehicle users must know how to manage their vehicle so their vehicles is always in a good condition.This application is created using Java programming language and using Android Studio application. The interface of this application uses Material Design. Backup and Restore feature uses Google Drive and Dropbox as online storage. Reminder feature uses Google Calendar as an event recording media.The final result of the application is that users can view their expenses as the result of using their vehicles. Besides, the users can save their data on the online storage without need to pay for anything.